(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the effectiveness of continuous oropharyngeal suctioning after extubation in patients with traumatic brain injury and to analyze factors related to intervention outcomes. Methods: A randomized clinical trial was conducted on 22 patients with traumatic brain injury after extubation at the Center of Anesthesiology and Intensive Care, Bach Mai Hospital, from April to October 2025. Patients were randomly assigned to either continuous oropharyngeal suctioning (n=11) or intermittent oropharyngeal suctioning (n=11). Outcome measures included the volume of secretions removed, number of suction catheters used, treatment outcomes, and procedure-related complications. Results: The continuous suctioning group showed a significantly higher and more stable volume of secretions removed over three days after extubation compared with the intermittent group (p<0.05), while using fewer suction catheters (p<0.05). No reintubation cases were observed in the continuous group, whereas one patient in the intermittent group required reintubation and tracheostomy. Nausea and vomiting were more frequent in the continuous group, while nasal and oral bleeding occurred more often in the intermittent group. Conclusions: Continuous oropharyngeal suctioning is an effective and safe intervention for airway secretion management and may reduce the risk of extubation failure in patients with traumatic brain injury.